Proposta de atualização nas instruções técnicas 28 e 29 do corpo de bombeiros militar do Rio Grande do Norte - Farias, Daniel Santos de (Universidade Federal Rural do Semi-Árido, 2019)
This work intends to gather the most current information on fire prevention in combustible gas installations and propose the insertion in the specific legislation in the state of Rio Grande do Norte, in this case, the technical instructions of the Fire Department. With the advent of the rapid advance of technology, public agencies can not be an obstacle in the economic-technological development when its role is of inspection. If safety is proven effective, the equipment or the installation must be provided for in technical standards, so that public servants, while respecting the constitutional principle of legality, can exercise their powers in the light of the latest technologies. For this, a research was done in the most varied norms of the area, evaluating their real applicability in commercial and residential buildings of the state, with the purpose of elaborating a proposal for a modern normative text. In order to have a safe scenario in buildings, updating the technical instructions of all safety measures has to be periodic at the heart of keeping abreast of new trends in engineering, keeping the standard in prevention.
Monografia
Keywords: Gás combustível; Atualização; Tecnologia; Combustible gas; Update; Technology; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA